Development of Peptic Ulcer following Second Shot of Sputnik V Vaccine: A Case Report and Literature Review of Rare Side Effects of Sputnik V Vaccine - Maryam Hasanzarrini; Amir Mohammad Salehi; Samira Nirumandi Jahromi (Case Reports in Infectious Diseases)
Considering the global spread of the coronavirus disease 2019 (COVID-19), it is expected that vaccination against its causative agent, the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), will reduce the related morbidity and mortality. However, the safety of the COVID-19 vaccines and their potential and unknown side effects are a matter of concern. With the ongoing development and implementation of COVID-19 vaccination programs around the world, the side effects, safety, and effectiveness of these vaccines are gradually being reported, providing researchers with valuable information that can affect the production and utilization of the COVID-19 vaccines. The present study intended to report a case of peptic ulcer disease (PUD) development following vaccination with Gam-COVID-Vac, a vector-based COVID‐19 vaccine containing two recombinant human adenoviruses (rAd26 and rAd5).